Analisis Kesalahan dan Tanda Baca pada Teks Biografi Presiden Indonesia dari Masa ke Masa dalam Website Liputan6.com Edisi Oktober 2024 sebagai Kelayakan Sumber Bacaan dan Sumber Informasi - Ferawati Sitompul; Arjun Dwi Rangga; Ahmad Zubair; Fina Halimatus Sholihah; Siti Wulandari; Asep Purwo Yudi Utomo; Vera Krisnawati; Yanuar Bagas Arwansyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Language determines the material that is taught. Language is an organized system of communication, which can be expressed either through speech or writing, and consists of units such as words, phrases, clauses, and sentences. Language is also a means of mediation between members of society who play an important role in shaping the cultural character of a nation. This research uses methodological and theoretical approaches. The approach focuses on in-depth observations based on the results obtained from the object of research that collects data, and there is no analysis of numerical or statistical data. The method that can be applied at the analysis stage consists of two types, namely the commensurate method and the agih method. The exemplary method is an independent method used to recognize certain linguistic units with the help of identifying tools that come from outside the language. While the AGIH method, the identifying tool, is precisely part of the language itself. This research applies a syntactic error analysis method to find out punctuation and spelling errors that often occur in biographical texts. The results of this study are expected to be an example for writers in writing various texts and reading materials. They can not be used as reference material for consideration in using good and correct punctuation. This research also aims to correct errors in the biography text of the President of Indonesia and maximize the quality of this biography text.